Sinergi Dosen FEB UTS Mendorong Literasi dan Inklusi Keuangan Para Santri di Pesantren Sumbawa - Rusni, Andi; Salam, Abdul; Aprirachman, Rozzy; Fietroh, Muhammad; Andriani, Sri; Purnama, Yuni; Sanjani, Muhammad Rafi'i; Nurjihadi, Muhammad; Irawan, Edi; Cita, Fitriah Permata; Nurasia, Nurasia; Oktapiani, Serli; Mandasari, Jayanti; Sugiarto, Aris; Nuryani, Hanifah Sri; Syahfitri, Diah Intan; Sari, Indah Fitriani (Civiliza Publishing, 2025)
This community service program at Pondok Pesantren Al-Mutmainnah aims to enhance conventional financial literacy and inclusion among santri (Islamic boarding school students) to equip them with the skills to manage personal finances wisely and independently. The method involved interactive material delivery using multimedia presentations, infographics, and educational videos, followed by discussion and Q&A sessions to reinforce understanding. Evaluation was conducted using pre-test and post-test questionnaires, showing a significant improvement with an average post-test score increase of 30 points compared to the pre-test. The discussion highlights that a participatory approach combined with visual media effectively improves santri’s knowledge, although challenges remain in understanding complex concepts such as investment and credit risk. The limited duration of the program also posed constraints on in-depth material coverage. Therefore, extended programs with longer duration and regular mentoring are necessary to ensure optimal internalization of financial attitudes and behaviors. Strengthening financial literacy is expected to contribute sustainably to the economic empowerment of the pesantren and the surrounding community.